The Increasing Official Characteristic Details Methods of The Technological Machines - Xolmatov Bakhtiyor; Shamayev Yigitali (Genius Journals, 2022)
The Problem of increasing to wear capability and longevity material worker mechanism agricultural machines is more actual. Defining importance in shaping the features to constructive toughness material worker mechanism agricultural machines has, as well known, variation of the structured condition. For this purpose article is studied structured conversions become under different type of the thermal processing, which vastly affect the specified characteristic.
Keywords: toughness; wear capability; toughnesslimit to fluidity